Impaired cerebral autoregulation detected in early prevasospasm period is associated with unfavorable outcome after spontaneous subarachnoid hemorrhage: an observational prospective pilot study - Edvinas Chaleckas; Vilma Putnynaite; Indre Lapinskiene; Aidanas Preiksaitis; Mindaugas Serpytis; Saulius Rocka; Laimonas Bartusis; Vytautas Petkus; Arminas Ragauskas (The Ultrasound Journal, 2024)
Abstract Background Subarachnoid hemorrhage (SAH) patients with cerebral autoregulation (CA) impairment at an early post-SAH period are at high risk of unfavorable outcomes due to delayed cerebral ischemia (DCI) or other complications. Limited evidence exists for an association between early-stage CA impairments and SAH patient outcomes. The objective of this prospective study was to explore associations between CA impairments detected in early post-SAH snapshot examinations and patient outcomes. Methods The pilot observational study included 29 SAH patients whose CA status was estimated 2–3 days after spontaneous aneurysm rupture and a control group of 15 healthy volunteers for comparison. Inflatable leg recovery boots (reboots.com, Germany) were used for the safe controlled generation of arterial blood pressure (ABP) changes necessary for reliable CA examination. At least 5 inflation‒deflation cycles of leg recovery boots with a 2–3 min period were used during examinations. CA status was assessed according to the delay time (∆TCBFV) measured between ABP(t) and cerebral blood flow velocity (CBFV(t)) signals during artificially induced ABP changes at boot deflation cycle. CBFV was measured in middle cerebral artery by using transcranial Doppler device. Results Statistically significant differences in ∆TCBFV were found between SAH patients with unfavorable outcomes (∆TCBFV = 1.37 ± 1.23 s) and those with favorable outcomes (∆TCBFV = 2.86 ± 0.99 s) (p < 0.001). Early assessment of baroreflex sensitivity (BRS) during the deflation cycle showed statistically significant differences between the DCI and non-DCI patient groups (p = 0.039). Conclusions A relatively small delay of ∆TCBFV <1.6 s between CBFV(t) and ABP(t) waves could be an early warning sign associated with unfavorable outcomes in SAH patients. The BRS during boot deflation can be used as a biomarker for the prediction of DCI. Trial registration ClinicalTrials.gov Identifier: NCT06028906. Registered 31 August 2023 - Retrospectively registered, https://www.clinicaltrials.gov/study/NCT06028906 .